2002
DOI: 10.1111/j.1469-445x.2002.tb00062.x
|View full text |Cite
|
Sign up to set email alerts
|

Bicarbonate‐induced alkalosis augments cellular acetyl group availability and isometric force during the rest‐to‐work transition in canine skeletal muscle

Abstract: Increasing blood bicarbonate content has long been cited as a potential mechanism to improve contractile function. We investigated whether sodium bicarbonate-induced metabolic alkalosis could positively affect force development during the rest-to-work transition in ischaemic skeletal muscle. Secondly, assuming it could, we investigated whether bicarbonate could augment acetyl group availability through the same equilibrium reaction as sodium acetate pre-treatment and whether this underpins, at least in part, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…4; Ref. 28). Indeed, bicarbonate treatment is known to be associated with an enhancement in muscular performance, especially during periods of high-intensity exercise of short duration (14), as has previously been described within this animal model (28).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4; Ref. 28). Indeed, bicarbonate treatment is known to be associated with an enhancement in muscular performance, especially during periods of high-intensity exercise of short duration (14), as has previously been described within this animal model (28).…”
Section: Discussionmentioning
confidence: 99%
“…A recent series of studies by our group has demonstrated the existence of metabolic inertia at the onset of contraction (27,28,(33)(34)(35)(36). On the basis of evidence from these studies, we believe that the delay in acetyl-CoA provision at the onset of exercise, which we have termed the "acetyl group deficit" (27), is a principal determinant of the oxygen deficit (27,33,34).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is in agreement with an in vitro study proposing that any strategy that increases the mitochondrial availability of acetyl groups and concomitantly increases blood bicarbonate content may improve the maintenance of contractile function. 2 This may also explain the observed increase of acetylcarnitine, 5 which is known to fluctuate during contraction according to acetyl-CoA availability. In agreement, Hollidge-Horvat et al 6 have reported a trend increase of acetyl-carnitine content in human skeletal muscle following sodium bicar-bonate ingestion.…”
Section: Discussionmentioning
confidence: 93%
“…Another mechanism by which bicarbonate may improve contractile function is by increasing the availability of acetyl-CoA towards the tricarboxylic acid cycle. 2 The aim of this study was to test whether a modified alkalizing supplementation could improve muscular metabolism and adaptation to exhaustive exercise in aged rats by examining either the gastrocnemius (fast muscle related to instantaneous force) and the soleus (slow muscle related to endurance).…”
Section: Introductionmentioning
confidence: 99%